Tv commercials and choice of food among children in Sabah, Malaysia - Andreas Totu; Oswald A. Igau; Murnizam Halik (2013)
This study examines the relationships between television (TV) advertising and patterns of food choice among children. This relationship is crucial in understanding the intricate interplay among several interrelated variables such as TV viewing, preference for certain foods and the problem of obesity. Specifically, the study investigates the degree of recognition of adverts and patterns of food choice among lean, overweight and obese children. This study uses an experimental test, but the assessment of the effects of advertisements was undertaken through questionnaires. There were 50 participants involved in the experiment. The outcomes of the study indicate that TV advertisements make a substantial contribution to what food a child chooses. Although there were some variations in terms of responses between age groups and gender, generally, children seemed likely to choose fast foods after treatment. Further analyses were performed which revealed that media, particularly TV advertising, appear to contribute significantly in terms of influencing children to choose fast food, followed by taste. The study also seems to suggest that there is a strong correlation between the weight of a child and food choice. In short, children who were inclined to choose fast foods tended to be overweight or obese.